PENDIDIKAN MULTIKULTURAL DI ERA POST TRUTH - Chori Miftahul Kosidatul Natus; Waston Waston; Ari Anshori; Mohammad Ali (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2022)
Purpose: This paper aims to discuss the implementation of multicultural education in the post truth era. Methodology: The methodology used in this paper is a qualitative study methodology, taken from literature relevant to the discussion of multicultural education in the post truth era. Results: In multicultural education there are three values ​​that can be applied, namely, the value of equality, tolerance, and harmony. The impact of post truth is the division in society if they cannot respond to post truth properly. One way is to internalize multicultural education in the curriculum and all members of the community who are in the environment of educational institutions participate in the success of multicultural education.